Degradation behavior of theophylline/chitosan/β-cyclodextrin microspheres for pulmonary drug delivery - Li Wang; Tingting Yang; Weiping Ju; Ming Ren; Zhanqin Feng; Zengjuan Zheng; Zhenbo Hu; Yuqing Liu; Weifen Zhang (Bangladesh Pharmacological Society, 2016)
To evaluate the degradation behavior of theophylline/chitosan/β-cyclo-dextrin microspheres, we performed both in vitro study by putting the microspheres in phosphate buffered saline or in phosphate buffer saline with enzyme and in vivo study by implanting the microspheres into the back of male Sprague-Dawley rats. The results showed that microspheres were degraded in enzymatic hydrolysis and phosphate buffer saline, which were degraded faster in 0.2 mg/mL lysozyme than in phosphate buffer saline. The morphology of microspheres in phosphate buffer saline and enzyme solution developed rough surfaces, and showed irregular shape and pores after 8 weeks. The microspheres were degraded in vivo within 8 weeks with irregular, sheet, porous morphology, and the diameters were smaller than 5 μm. These results indicated that the theophylline/chitosan/β-cyclodextrin microspheres had a good degradation both in vitro and in vivo which can be used as a pulmonary drug delivery carrier.